Cultural sensitivity in forensic services: Findings from an audit of South London forensic inpatient services - Warnock-Parkes, E; Young, S; Gudjonsson, G (2010)
This paper summarises the key findings from an audit using the Cultural Sensitivity Audit Tool for Mental Health Services (The Sainsbury Centre for Mental Health, 2001) to evaluate the views of service-users and staff in a South London Forensic Inpatient Service. Forty-one service-users and 47 members of staff working in the service took part in the audit. Staff completed the tool as a questionnaire, and service-users were interviewed. The majority of staff believed that black and minority ethnic patient groups were over-represented in the service, and many attributed this to misunderstandings of culture. Staff identified gaps in their training on race and culture; none of the staff believed they had received all the training required. Nevertheless, service-users highlighted culturally sensitive and effective aspects of the service, and many believed their cultural needs were understood. Given this disparity, the authors question whether the large emphasis on the cultural sensitivity of services is something service-providers are more concerned about than our service-users; and whether a greater focus on service quality, of which cultural sensitivity is one aspect, would be more helpful. © 2010 Taylor and Francis.